Tides of fire [compact disc, unabridged] - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2023)
To stop the world from burning, it's up to Sigma Force to uncover a secret buried at the heart of our planet. The Titan Project-an international research station off the coast of Australia-discovers a thriving zone of life in an otherwise dead sea. The area teems with a strange bioluminescent coral that defies science, yet holds great promise for the future. But the loss of a military submarine in the area triggers a brutal attack and sets in motion a geological disaster that destabilizes an entire region. Massive quakes, volcanic eruptions, and deadly tsunamis herald a greater cataclysm to come-for something is stirring miles under the ocean, a threat hidden for millennia. As seas turn toxic and coastlines burn, can Sigma Force stop what has been let loose-especially as an old adversary returns, hunting them and thwarting their every move? For any hope of success, Commander Gray Pierce must search for a key buried in the past, hidden deep in Aboriginal mythology. But what Sigma could uncover is even more frightening-something that will shake the very foundations of humanity.